The Urgency Of Imposing Excise On Sugar-Sweetened Beverages - Rusdiono, Leander Resadhatu (Jurnal Pajak dan Keuangan Negara (PKN), 2023)
In Indonesia, one of the causes of obesity and diabetes is the high consumption of sugar-sweetened beverages with a high sugar content. The high incidence of obesity and diabetes has made it imperative for the Indonesian government to impose an excise tax on these sugary beverages in order to reduce sugar consumption and prevent the spread of disease in the country. This study aims to analyze the urgency of imposing excise duty on sugar-sweetened beverages, which has been implemented in a number of other countries. For the purpose of comparing current conditions to those of previous studies, qualitative data collection techniques and library research were employed to gather the necessary information. In several countries that have implemented the SSB Tax (Sugar-Sweetened Beverage Tax), the application of an excise duty on sugar-sweetened beverages has been associated with a reduction in consumption, as determined by the results of the analysis. Reducing consumption will have an effect on reducing the number of cases of disease attributable to excessive sugar consumption and will become an alternative means of achieving the state's revenue goals. However, prior to implementing an excise tax on sugar-sweetened beverages, the government must conduct a thorough analysis of the potential consequences.